Análisis de los segmentos infantil y juvenil del proyecto educa en la identidad cultural en los Jòvenes de 12 a 17 años de la parroquia Santiago de Quito del cantón Colta, durante el período enero-junio de 2016 - Verdezoto, Victor (2017)
In this research, young people between the ages of 12 to 17 were analyzed in terms of cultural identity in the parish Santiago de Quito, Colta County, during the period January – June 2016. Existing cultural practices in teenagers were identified. The theory was based on the hypodermic needle which looks to inject its contents into the mentalities of young people thus changing their ideologies, also which is functionalist in the means of communication because it studies the influence of communication means among the masses, the obtained results demonstrate that the project does not influence in the main part of young people’s cultural identity since 50% percent of the programs take up one hour weekly and are thus broadcast at 16:00. The methodology which was used in this current research was descriptive since it details cultural behaviors in terms of the studied population regarding gender, traditions, religion, vestment, music, among others. It is also a field research since the place was visited. Cultural identity is conserved thanks to other variables such as the environment were the everyday situations that take place which are present among the inhabitants. The most viewed segments are Veo Veo, Marcela Aprende Kichwa, and Mi Voz Mi Mundo. Another of the fundamental aspects which collaborate with the hold of cultural identity is the transmission of cultural ideas throughout distinct generations or education which maintains itself intercultural.